(untitled) (The Review of Diabetic Studies, 2025)
The multidisciplinary team has emerged as an important determinant of patient outcomes in an acute care setting, where the complexity of clinical scenarios, physiological worsening conditions, and time-sensitive treatments require the coordinated expertise of multidisciplinary teams. This study investigates the role of combined effort involving pharmacy, radiology, respiratory therapy, nursing, paramedics, operating room (OR) technology and infection control in enhancing patient safety, accuracy in diagnoses, efficiency of treatment and overall patient clinical outcomes. The paper examines the distinct input of each field using a review of peer-reviewed literature, clinical guidelines, and evidence-based models and presents how collaborative practices can optimize care delivery. The evidence suggests that in the case of efficient communication between acute care teams, joint responsibilities in decision making, and awareness of professional roles, the rates of medical errors, harm caused by medications, delays in diagnosis, hospital-acquired infections, and death rate decrease significantly. Also, the level of workflow efficiency, minimization of redundancy, and more ethical and patient-focused care are more supported by a collaborative environment. Case studies also demonstrate that interdisciplinary coordination, e.g. pharmacist-assisted medication reconciliation, radiology-based rapid diagnostics, respiratory therapist involvement in early ventilation planning and integration of infection control during invasive interventions directly impact patient recovery trajectories. In spite of its positive aspects, interdisciplinary collaboration is not without challenges such as lack of role clarity, hierarchical culture, communication failures, and lack of professional training. This paper will end with a set of strategic suggestions supported by standardized communication structures, interprofessional education based on simulation, organizational policy change, and leadership development. On the whole, the study highlights the importance of interdisciplinary collaboration as it is not a choice but a prerequisite of high-quality, safe, and holistic acute care.